Improving Global Road Safety : Towards Equitable and Sustainable Development, Guidelines for Country Road Safety Engagement - Bliss, Tony (World Bank, Washington, DC, 2014)
The sheer scale of health losses from road crashes makes road safety a development priority for the health and transport sectors of low and middle-income countries (LMICs). Poorer population groups bear a disproportionate burden of these health losses which are generally influenced by socio-economic factors and other social and environmental determinants, and increasing emphasis is being placed on global health promotion and equity as a core, crosscutting development strategy. Country development aims to promote higher living standards for all, with an emphasis on improved health, education and people's ability to participate in the economy and society. Improving road safety in LMICs contributes to the achievement of these development goals by addressing the vulnerability of citizens to catastrophic death and injury arising from road crashes and requires large-scale investments in infrastructure, institutions, vehicle fleets and the health and wellbeing of individuals. World Bank road safety projects have usually been components of larger road infrastructure and urban transport investment operations, and implemented as fragmented, single-sector initiatives. However, it became evident that a focus on measurable results and longer-term sustainability was critical to success. Hence the World Bank is now promoting safe system road safety projects that aim to simultaneously strengthen institutional capacity and accountability while seeking rapid improvements in safety performance for all road users. Country guidelines have been prepared to support this new approach. This report summarizes such guidelines for country road safety engagement.